The biopore’s movement as flood prevention in Sungai Nangka Village, Balikpapan - Muhammad Ma'arij Harfadli; Dhany Achmad Wicaksono; Qamara Daffa; Rafi Zaidan Mahdy (University of Merdeka Malang, 2022)
Flooding can be defined as the submergence of a place because a high overflow of water exceeds the water capacity of an area. In Balikpapan, many areas are still inundated during heavy rains. Especially in Pondok Karya Agung Housing RT.18 Sungai Nangka Village, flooding is a major problem that occurs in the area. This community service program aims to increase community knowledge about flood prevention at Pondok Karya Agung Housing RT.18 Sungai Nangka Village. Methods of implementation in these services socialized and practiced planting biopore infiltration holes. The implementation phase includes preparation, implementation, and evaluation of increasing participants' understanding of making biopore infiltration holes. This community service program was attended by 25 participants. There are 24 points for biopore locations. These activities will be held for two days. The results show that understanding and interest in implementing increased after the socialization and practice of installing biopore infiltration holes.